1979
DOI: 10.1139/f79-155
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Chlorine, Temperature Change (ΔT), and Exposure Time on Survival of Striped Bass (Morone saxatilis) Eggs and Prolarvae

Abstract: Effects of total residual chlorine (TRC), change in temperature (ΔT), and exposure time were established for eggs and prolarvae of striped bass, Morone saxatilis, under test conditions designed to simulate entrainment by power plants. Prolarvae were found to be more sensitive than eggs under the same test conditions. In contrast to the predominant effect of TRC and exposure time on eggs, TRC and ΔT and exposure time were all found to be important in causing mortality of prolarvae. The study shows that in an ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1981
1981
1990
1990

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…These investigators reported that TRC and exposure duration were the predominant factors that caused mortality to striped bass eggs. Although the study designs by Burton et al (27,28) were different from those of the present study, isolated exposures of 0.30 mg/L TRC caused ~84% mortality after 4 h of continuous exposure in the Burton et al studies (27,28) while 100% mortality occurred at 36 h in the present investigation.…”
Section: Discussioncontrasting
confidence: 64%
“…These investigators reported that TRC and exposure duration were the predominant factors that caused mortality to striped bass eggs. Although the study designs by Burton et al (27,28) were different from those of the present study, isolated exposures of 0.30 mg/L TRC caused ~84% mortality after 4 h of continuous exposure in the Burton et al studies (27,28) while 100% mortality occurred at 36 h in the present investigation.…”
Section: Discussioncontrasting
confidence: 64%
“…It is clear that the prolarval stage is the most sensitive early life stage of striped bass exposed to BKME. Other investigators have also shown that prolarvae of striped bass are more sensitive than eggs or larvae exposed to other toxicants (Morgan and Prince, 1977;Middaugh, et d.. 1977;Burton, et d., 1979;Hall, et aZ., 1981). It appears that treated BKME effluents (8 to 12 percent (v/v) with BODS, TSS, and true color concentrations ranging from 1.5 to 2.0, 15 to 22, and 140 to 210 mdl, respectively, may be important effluent limitations for eliminating direct impact to the early life stages of striped bass.…”
mentioning
confidence: 94%
“…limited studies on the toxicity of treated bleached kraft mill effluent (BKME) and its effects on the production and growth of warm water fish suggest that treated effluent should havc minimal impact on fish populations (e.g., Juul and Shireman, 1978; National Council of the Paper Industry for Air and Stream Improvement, lnc., 1978; d, 19-1 1. "his implies that treated BKME should not affect the early life stages of f&. It is well established that the early life stagea of f & are generally more sensitive to pollutants than dder life stages ( Rosenthal and Alderice, 1976;M c h , 1977;Burton, et d, 1979). lhis study was initiated becruse of the paucity of data on the toxicological effects of treated BKME on the critical early life stages of warm water fish.…”
Section: Introductionmentioning
confidence: 99%
“…(1) physiological effects (Buckley, et al, 1976;Middaugh, et al, 1977;Scott and Middaugh, 1978); (2) morphological defects (Thatcher, 1979); (3) interaction of chlorine-AT exposure time (Middaugh, et d., 1978;Burton, et aL, 1979;Hall, et d., 1981); (4) avoidance responses of fish species tochlorine (Meldrim, et al, 1974;Meldrim and Fava, 1977);and (5)avoidance responses of fish species exposed to a range of simultaneous chlorine-AT conditions (Hall, et d., in press). In the present study, a behavior response (avoidance) was used as a method of evaluating sublethal chlorine effects.…”
Section: Introductionmentioning
confidence: 99%